Head first Java - Sierra, Kathy; Bates, Bert.; Gee, Trisha (Sebastopol, CA : O'Reilly, 2022)
"Head First Java" engages readers on many levels, bringing the latest learning theories and research together to create not just a book to read, but a multi-sensory learning experience.
"Head First Java is a complete learning experience in Java and object-oriented programming. With this book, you'll learn the Java language with a unique method that goes beyond how-to manuals and helps you become a great programmer. Through puzzles, mysteries, and soul-searching interviews with famous Java objects, you'll quickly get up to speed on Java's fundamentals and advanced topics including lambdas, streams, generics, threading, networking, and the dreaded desktop GUI. If you have experience with another programming language, Head First Java will engage your brain with more modern approaches to coding--the sleeker, faster, and easier to read, write, and maintain Java of today." -- Back cover.
Breaking the surface -- A trip to objectville -- Know your variables -- How objects behave -- Extra-strength methods -- Using the Java library -- Better living in objectville -- Serious polymorphism -- Life and death of an object -- Numbers matter -- Data structures -- What, not how -- Risky behavior -- A very graphic story -- Work on your swing -- Saving objects (and text) -- Make a connection -- Dealing with concurrency issues.
Includes index.
"A learner's guide to real-world programming"--Cover.
"Covers Java 8-17" -- Cover.
"A brain-friendly guide" -- Cover.
Keywords: Java (Computer program language); Programming languages (Electronic computers); Handbooks and manuals; Instructional and educational works; Handbooks and manuals